PKM Melalui Pelatihan Menyusun Laporan Penelitian Tindakan Kelas - Farah Pahrunnisa; Santi Dwi Handayani; Sherly Damayanti Fazrin (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
The competency to conduct Classroom Action Research for elementary school teachers is a very importantpedagogical competency that must be mastered as one of the teacher's professional competencies. However,in reality these competencies are still poorly understood and mastered by educators, especially teachers atthe elementary school level. Even when they have to make PTK reports, the teachers experience difficulties.To help teachers overcome their difficulties, we, students of the STKIP Kusuma Negara Bekasi in elementaryschool teacher education study program, have carried out a Community Service and Empowerment activityentitled